Reworking Potential of Polyvinylpyrrolidone K-25 as a Binder in The Production of Paracetamol Tablets - Agatha Budi Susiana Lestari; Okana, Lie Dofi Ananda Madelin (Journal of Fundamental and Applied Pharmaceutical Science, 2025)
Binding agents play an important role in maintaining the bond between active and additional ingredients in tablets, especially when subjected to repeated compression. One commonly used binder is polyvinylpyrrolidone (PVP) K-25. However, issues often arise regarding the binder's potential when undergoing multiple compressions. This research, hence, aims to determine the reworking potential of PVP K-25 with different concentration levels as a binder, focusing on the physical properties of the mixtures and the resulting paracetamol tablets. The study follows a pure experimental design with a two-way completely randomized research design. Tablets were compressed and subsequently crashed again twice. Various tests, including flow properties and compressibility for the mixtures, as well as compatibility, hardness, friability, and disintegration time for the tablets, were conducted to assess their physical properties. The obtained data were subjected to statistical analysis, starting with the Shapiro-Wilk normality test, followed by Kruskal-Wallis and Post-Hoc Mann-Whitney tests. The research findings indicate that PVP K-25 can maintain its potential as a binder, as evidenced by the physical properties of both the mixtures and the resulting paracetamol tablets.